Motor learning and performance a situation-based learning approach ; [includes access to online study guide ; 20 experimental labs] - Schmidt, Richard A. 1941-2015 (Human Kinetics, 2008)
"Motor Learning and Performance: A Situation-Based Learning Approach outlines the principles of motor skill learning, develops a conceptual model of motor performance, and shows students how to apply the concepts of motor learning and performance to a variety of real-world settings. This fourth edition includes access to an online student study guide with lab activities that bring the material to life."--BOOK JACKET